An Experimental Investigation of Using Sisal Fiber and Coir Fiber as An Additive in Stone Matrix Asphalt - Mustafa Musleh Razahi, Avani Chopra (International Journal of Advanced Science and Technology, 2020)
Stone matrix asphalt is a hard, sturdy, stable and persistent blend that depends on a stone-to-stone bond for its force and a rich mortar binder for its strength. Stone Matrix Asphalt (SMA) is a gap-graded mixture composed of 70-80 percent coarse aggregate, 8-12 percent filler, 6.0-7.0 percent binder, and 0.3-0.5 percent fiber. SMA was first developed in Europe to reduce the rutting induced by the use of studded tires. Owing to its progress in Europe, in cooperation with the Federal Highway Administration, the United States of America (USA) has also initiated the development of SMA pavements in some states. SMA has a potential problem of drain down during transport and laying. However to reduce the drain down of stone matrix asphalt the fibers are used as additives in SMA which may either be chemical or natural fibers. In the present study, Sisal fiber and Coir fiber are used as additives in the stone matrix asphalt mixture. to evaluate and compare these two fibers in SMA mixture and determining the stability, flow, and volumetric properties by performing the Marshall Stability Test. By varying the percentages of bitumen from 5.5%, 6%, 6.5%, and 7%, the Optimum Bitumen Content was found to be 6.1%. The dosages of sisal fiber and coir fiber are 0.2%, 0.3%, 0.4% and 0.5% by total weight of aggregate and Optimum Fiber Content was found to be 0.3% for both sisal fiber and coir fiber. It was found that the addition of sisal fiber and coir fiber to SMA mixes contributed significantly in improving SMA mix efficiency. In this investigation various tests were conducted such as drain down test to obtain the amount of drain down in uncompacted SMA mixes, Indirect Tensile Strength Test (ITS) to determine the tensile strength of stone matrix asphalt mixes with and without fibers.